Changing serum creatinine in the detection of acute renal failure and recovery following radiocontrast studies among acutely ill inpatients: Reviewing insights regarding renal functional reserve gained by large-data analysis - Yuri Gorelik; Zaid Abassi; Natalie Bloch-Isenberg; Mogher Khamaisi; Samuel N. Heyman (Practical Laboratory Medicine, 2022)
A rise in serum creatinine (SCr) is widely used for the detection and definition of evolving acute kidney injury (AKI). Yet, it takes time for SCr to re-adjust in response to changes in glomerular filtration rate (GFR), and subtle transient changes in GFR may remain concealed. Additionally, it cannot differentiate altered glomerular hemodynamics and pre-renal failure from true renal tissue injury, necessitating additional clinical and laboratory diagnostic tools.While these features limit the usefulness of SCr and subsequently estimated GFR (eGFR) at a single time point for the individual patient, their overall pattern of changes along time in a large cohort of hospitalized patients may provide a powerful perspective regarding the detection and assessment of shifting kidney function in this population. Herein we review our experience running large data analyses, evaluating patterns of day-to-day changes in SCr among inpatients, occurring around the exposure to iodinated radiocontrast agents. These large data evaluations helped substantiating the existence of contrast-induced nephropathy in patients with advanced renal failure, underscoring the impact of predisposing and confounding factors. It also provides novel insights regarding a phenomenon of ''acute kidney functional recovery” (AKR), and illustrate that the incidence of AKI and AKR along the scale of baseline kidney function co-associates and is inversely proportional to kidney function. This can be attributed to renal functional reserve, which serves as a buffer for up-and-down changes in GFR, forming the physiologic explanation for concealed subclinical AKI.